Report on Candidates' Work in the Secondary Education Certificate General Proficiency Examination June 1989: English B - Caribbean Examinations Council (CXC, 1989)
This report contains general and specific comments on the performance of candidates in the June 1989 Caribbean Secondary Education Certificate (CSEC) general proficiency examinations in English B.
Keywords: CXC CSEC examinations